Choledochoduodenal fistula secondary to duodenal ulcer disease and choledocholithiasis: Report of 2 cases - Al-Aziz, Md Zakaria; Ahmed, Mashrafi; Siddiqui, Md Mahmudur Rahman; Shipa, Md Ruhul Amin; Sarker, Symal; Arif, Syed Md; Siddiqui, FM (Journal of Armed Forces Medical College, Bangladesh, 2009)
doi:10.3329/jafmc.v4i2.1845 JAFMC Bangladesh Vol.4(2) 2008 38-41